Is It Safe to Restart Antivascular Endothelial Growth Factor Therapy in Patients with Renal Cell Carcinoma after Cardiac Ischemia? - Bo Zhao; Laura S. Wood; Karen James; Brian I. Rini (Case Reports in Oncological Medicine)
Agents targeting vascular endothelial growth factor (VEGF) represent active drugs in treating patients with advanced renal cell carcinoma (RCC). Studies have shown that sunitinib and axitinib can be associated with cardiac toxicity. Whether these agents should be restarted in patients who experience cardiac ischemia remains uncertain. Here, we present three patients with metastatic RCC who restarted sunitinib or axitinib after intervention of active ischemic cardiac disease without causing subsequent relevant cardiac events. This experience suggests that these agents can be continued after management of cardiac ischemia.